Modified Zero Overloading Policy Impact to Pavement’s Service Life - Reni Karno Kinasih; Mukhlisya Dewi Ratna Putri; Nabila Nabila (Engineering, MAthematics and Computer Science (EMACS) Journal, 2020)
Indonesia have not finished yet with the overloading truck problem which makes early failure in Indonesia pavements, mainly in national highways such as Pantura national highway. This is the first research which the aim is to compare the Cumulative Equivalent Single Axle Load (CESA) between 4 policy conditions; (1) zero overloading policy enforced; (2) modified 1 zero overloading policy enforced with 40% legal overloading tolerance for the nine-daily needs (rice, sugar, cooking oil, soy beans, salt, meat, chicken, eggs, onion), portland cement and fertilizer trucks; (3) modified 2 zero overloading policy enforced with 50% legal overloading tolerance for the same transporter as point (3); (4) no policy. This modification of the policy considered to avoid the price increment of those goods caused by the rising expedition cost. The Liddle’s formula used with k–factor = 1 for single axles, 0.086 and 0.031 for tandem and tridem axles. The finding of the study shows decreasing CESA between the alternatives compare to no policy applied. Application of policy 2 and 3 reduce the CESA number as much 44% and 34% respectively, there is 10% displaced cargo difference between policy 2 and 3 which must be loaded to other vehicles